Physical, mental and healthcare issues of children on the street of Ibadan, Nigeria - Abimbola M. Obimakinde; Moosa Shabir (AOSIS, 2023)
Background: Most street children studied in lower- and middle-income African countries are without family links. However, the majority of street children are children on the street, living with families during the night and spending their day-time on the streets. The health of this majority group is poorly captured in the literature despite the growing epidemic of child streetism. Aim: To explore the health of children on the street of Ibadan using multiple qualitative studies. Setting: A street in each of the five urban local government areas of Ibadan Oyo State, Nigeria. Methods: Participants comprising of children on the street, parental figures, street shop owners and child-welfare officers were purposively selected and interviewed. Interviews were audio recorded, transcribed, and thematically analyzed. Results: Using triangulated data from 53 interviews, the study found that the children on the streets of Ibadan experienced many health challenges. Outstanding are poor carbohydrate-based diet, open defaecation with consequent infections, physical injuries and few deaths from road traffic accidents. Sexual, verbal and substance abuse were common although few children acquired resilience to adversity. The children had poor health-seeking behaviour and resorted to patent medicine dealers or tradomedical practitioners on the streets. Conclusion: This study bridged some gaps in the literature regarding the health of children on the streets in Nigeria. The straddling of children between the family and street has cumulative health consequences as depicted in this study. Contribution: This research can inform family-level intervention and primary health care plans to forestall the health challenges of children on the streets.